Programming material compliance and actuation: hybrid additive fabrication of biocomposite structures for large-scale self-shaping. (26th July 2021) - Cheng, Tiffany; Wood, Dylan; Kiesewetter, Laura; Özdemir, Eda; Antorveza, Karen; Menges, Achim
Abstract: We present a hybrid approach to manufacturing a new class of large-scale self-shaping structures through a method of additive fabrication combining fused granular fabrication (FGF) and integrated hygroscopic wood actuators (HWAs). Wood materials naturally change shape with high forces in response to moisture stimuli. The strength and simplicity of this actuation make the material suitable for self-shaping architectural-scale components. However, the anisotropic composition of wood, which enables this inherent behavior, cannot be fully customized within existing stock. On the other hand, FGF allows for the design of large physical parts with multi-functional interior substructures as inspired by many biological materials. We propose to encode passively actuated movement into physical structures by integrating HWAs within 3D-printed meta-structures with functionally graded stiffnesses. By leveraging robotic manufacturing platforms, self-shaping biocomposite material systems can be upscaled with variable resolutions and at high volumes, resulting in large-scale structures capable of transforming from flat to curved simply through changes in relative humidity.